Effect of microwave-activated crumb rubber on reaction mechanism, rheological properties, thermal stability, and released volatiles of asphalt binder. (1st March 2020) - Yang, Xiaolong; Shen, Aiqin; Li, Bo; Wu, Hansong; Lyu, Zhenghua; Wang, Han; Lyu, Zhenfeng
Abstract: Waste crumb rubber (CR) can be used in asphalt pavement construction to develop eco-friendly and sustainable pavements. The objective of this study was to investigate the reaction mechanism, high-temperature properties, thermal stability, and volatiles released by CR-modified asphalt (CRMA) activated using microwaves (i.e., ACRMA). The chemical characteristics determined via Fourier-transform infrared spectroscopy revealed that mainly physical reactions occurred in the CRMA before and after activation; however, the swelling reaction in the ACRMA was more efficient than that in the CRMA. These results were confirmed by gel permeation chromatography and atomic force microscopy. The high-temperature performance of the ACRMA was slightly better than that of the CRMA. Additionally, according to stress creep and recovery test results, the microwave activation reduced the stress sensitivity of the rubber-modified asphalt. Thermogravimetric curves indicated that the microwave activation reduced the decomposition temperature of the rubber-modified asphalt. Moreover, the total amount of released volatiles for the base asphalt was significantly larger than that for rubber-modified asphalts, indicating that the CR suppressed the total amount of released volatile gases from the asphalt during the pyrolysis of asphalt. But the addition of CR can increase the release of some toxic gases in CRMA and increase the toxicological potential of asphalt fumes. However, in the initial pyrolysis of rubber asphalts, microwave treatment can reduce the generation of toxic gases. In the later stages of this process, the introduction of rubber particles before and after activation has little effect on the released volatiles.